Psychological resilience and death preparation in later life: associations from the health and retirement study - Jinjing Chen; Ruifang Zhao; Yan Dou; Weile Ma; Yong Wang; Bing Li (BMC Psychology, 2026)
Abstract Background Death preparation is an essential yet understudied aspect of psychological and behavioral adaptation in later life. Understanding how psychological resilience and health perception shape end-of-life planning can inform strategies to promote autonomy and well-being among older adults. Methods Data were drawn from the 2018–2022 waves of the Health and Retirement Study (HRS), including 26,532 participants aged 65 and older. Logistic regression and sensitivity analyses were conducted to examine the associations of demographic, health, and psychological factors with death preparation, with psychological resilience as the primary predictor. Results Approximately 60% of respondents reported engaging in at least one form of death preparation. Higher preparation rates were observed among older, better-educated, and functionally limited individuals, while those reporting better self-rated health were less likely to prepare. A pattern consistent with an inverse association between psychological resilience and death preparation was observed, particularly among the oldest-old, and remained significant after adjustment for covariates. Conclusions Death preparation was associated with demographic, health, and psychological factors in later life. Greater psychological resilience was consistently associated with a lower likelihood of death preparation, although the mechanisms underlying this association remain unclear. These findings highlight the importance of considering psychological factors in end-of-life planning and support further longitudinal and cross-cultural research to clarify the mechanisms underlying these observed associations. Trial registration This study is a secondary analysis of data obtained from a public database and did not involve a prospective clinical trial. Therefore, clinical trial registration is not applicable.